2014
DOI: 10.1364/ol.39.001145
|View full text |Cite
|
Sign up to set email alerts
|

Terbium gallium garnet ceramic Faraday rotator for high-power laser application

Abstract: A terbium gallium garnet (TGG) ceramic Faraday rotator (FR) with an isolation ratio of 33 dB was demonstrated at a laser radiation power of 257 W. This FR can be equipped with a large optical aperture by using ceramics technology to prevent laser damage at high-energy pulse operation. The thermal lens of a 257 W laser with a beam diameter of 2.6 mm had a focal length of 9.5 m, which is easily corrected using a spherical lens to suppress the undesirable effects of thermal lensing. The rotation angle of the FR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 24 publications
1
25
1
1
Order By: Relevance
“…High-purity Tb 4 and sintered for 12 h at 1200-1400°C. Such formed materials were crushed, re-mixed and sintered again at 1200-1400°C or 24 h. Finally, we obtained polycrystalline materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-purity Tb 4 and sintered for 12 h at 1200-1400°C. Such formed materials were crushed, re-mixed and sintered again at 1200-1400°C or 24 h. Finally, we obtained polycrystalline materials.…”
Section: Methodsmentioning
confidence: 99%
“…Magneto-optical materials used in FIs are mainly crystals or ceramics with high Verdet constants (V), high thermal strength for high average power, low absorption coefficient, high damage threshold and size scalability [3,4]. For long distance communications, yttrium iron garnet (YIG) with high transparency in the infrared region is employed and it is characterized by a very large rotation angle of the polarization plane (about 220°/cm at 1300 nm [5,6]).…”
Section: Introductionmentioning
confidence: 99%
“…1. These ceramic samples were studied in several recent works: TGG [6][7][8][9], TAG [10][11][12]. The techniques for measuring thermally induced depolarization and thermal lens were the same in all the studies.…”
Section: Depolarization In Ceramicsmentioning
confidence: 99%
“…For TGG, the length coincided with the required one. The plots for the optical power of thermal lens as a function of the laser power obtained in [7,10,12] and recalculated for the length L = L 45 and the beam with a diameter of 2.4 mm are presented in Fig. 4.…”
Section: Thermal Lens In Ceramicsmentioning
confidence: 99%
“…The investigation of both pure and doped TAG transparent ceramics in recent years also showed that the isolation ration, thermally induced depolarization and thermal lens were all superior to or comparable with the most commonly used Tb 3 Ga 5 O 12 (TGG) single crystals [9][10][11][12]. Furthermore, the excellent size scalability of transparent ceramics could prevent laser damage in these high energy systems [13,14,15]. So far, scattering is the only drawback that impedes the practical application of TAG, so it is urgent to improve its optical qualities [12].…”
Section: Introductionmentioning
confidence: 99%